Hygienic evaluation of physical risks in the timber sector in Ecuador - Barragán Monrroy, Roberto (2021)
The objective of this research was to evaluate the physical risks to which personnel working in the production and industrial processes of the timber sector are exposed. Two critical areas of human resource performance were identified in the industries for the hygienic evaluation. In these areas, corresponding to planning and sawing, machines and tools that are in constant operation, covering the entire workday. The research methods considered were observation, field, quantitative, interviews, and methodologies available from the National Institute of Safety and Hygiene at Work of Spain, complemented by technical noise guides calculating the equivalent daily exposure level, uncertainty, and attenuation. Lighting was analyzed by taking measurements at eight key points taking into account the legal values according to the industrial sector, and vibrations by calculating acceleration and daily exposure values. The risk levels found in the evaluations comply with the legal limits established in the regulations in force, except for vibrations, affecting the hand-arm system and representing considerable risk situations for workers.